China's business cycles: Perspectives from an AD-AS model - Yin Zhang; Guanghua Wan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
This paper represents a first attempt to study China's business cycles using a formal analytical framework, namely, a structural VAR model. It is found that: (a) demand shocks were the dominant source of macroeconomic fluctuations, but supply shocks had gained more importance over time; (b) the driving forces of demand shocks were consumption and fixed investment in the first cycle of 1985–90, but shifted to fixed investment and world demand in the second cycle of 1991–96 and the post-1997 deflation period; and (c) macroeconomic policies did not play an important part either in initiating or counteracting cyclical fluctuations.
Keywords: E32; O53; P24; 330; business cycle; structural VAR; demand shocks; supply shocks; China; Konjunktur; Schock; VAR-Modell; China